ASSOCIATION BETWEEN TOXOPLASMA GONDII INFECTION IN WOMEN AND THE PRESENCE OF CARDIOLIPIN AND PHOSPHOLIPID ANTIBODIES - N. A’aiz, Noaman; A. Sultan, Baqur; Al-Fatlawi, Sabah M.; Mahmood, Abdulkareem A. (European Scientific Journal, ESJ, 2014)
IgG and IgM cardiolipin and phospholipid antibodies were measured, by an ELISA technique, in the sera of patients with toxoplasmosis. Immunological methods for autoantibodies had been applied by ELISA. Regarding Anti-cardiolipin it was revealed that 24.7% of toxoplasmosis cases versus 0% of control group showed significant positive result (P=0.0412) . Whereas, 12.5% of toxoplasmosis patients and 12% of healthy controls had anti-cardiolipin antibodies, with no significant differences (P=0.554) between these two groups.